Bat*21 [videorecording (DVD)] - Markle, Peter; Glover, Danny; Hackman, Gene; Reed, Jerry; Anderson, William C., 1920-2003 (MGM Home Entertainment, 2000)
Vietnam, 1968. A true story of a middle-aged air force officer, LTC Iceal Hambleton, who's never seen combat before. He is stranded behind enemy lines and all he can do is wait and hope. Then a voice crackles over his radio, and he has found a friend.